If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22x(3x + 4) = 484 Reorder the terms: 22x(4 + 3x) = 484 (4 * 22x + 3x * 22x) = 484 (88x + 66x2) = 484 Solving 88x + 66x2 = 484 Solving for variable 'x'. Reorder the terms: -484 + 88x + 66x2 = 484 + -484 Combine like terms: 484 + -484 = 0 -484 + 88x + 66x2 = 0 Factor out the Greatest Common Factor (GCF), '22'. 22(-22 + 4x + 3x2) = 0 Ignore the factor 22.Subproblem 1
Set the factor '(-22 + 4x + 3x2)' equal to zero and attempt to solve: Simplifying -22 + 4x + 3x2 = 0 Solving -22 + 4x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -7.333333333 + 1.333333333x + x2 = 0 Move the constant term to the right: Add '7.333333333' to each side of the equation. -7.333333333 + 1.333333333x + 7.333333333 + x2 = 0 + 7.333333333 Reorder the terms: -7.333333333 + 7.333333333 + 1.333333333x + x2 = 0 + 7.333333333 Combine like terms: -7.333333333 + 7.333333333 = 0.000000000 0.000000000 + 1.333333333x + x2 = 0 + 7.333333333 1.333333333x + x2 = 0 + 7.333333333 Combine like terms: 0 + 7.333333333 = 7.333333333 1.333333333x + x2 = 7.333333333 The x term is 1.333333333x. Take half its coefficient (0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. 1.333333333x + 0.4444444442 + x2 = 7.333333333 + 0.4444444442 Reorder the terms: 0.4444444442 + 1.333333333x + x2 = 7.333333333 + 0.4444444442 Combine like terms: 7.333333333 + 0.4444444442 = 7.7777777772 0.4444444442 + 1.333333333x + x2 = 7.7777777772 Factor a perfect square on the left side: (x + 0.6666666665)(x + 0.6666666665) = 7.7777777772 Calculate the square root of the right side: 2.788866755 Break this problem into two subproblems by setting (x + 0.6666666665) equal to 2.788866755 and -2.788866755.Subproblem 1
x + 0.6666666665 = 2.788866755 Simplifying x + 0.6666666665 = 2.788866755 Reorder the terms: 0.6666666665 + x = 2.788866755 Solving 0.6666666665 + x = 2.788866755 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = 2.788866755 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = 2.788866755 + -0.6666666665 x = 2.788866755 + -0.6666666665 Combine like terms: 2.788866755 + -0.6666666665 = 2.1222000885 x = 2.1222000885 Simplifying x = 2.1222000885Subproblem 2
x + 0.6666666665 = -2.788866755 Simplifying x + 0.6666666665 = -2.788866755 Reorder the terms: 0.6666666665 + x = -2.788866755 Solving 0.6666666665 + x = -2.788866755 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = -2.788866755 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = -2.788866755 + -0.6666666665 x = -2.788866755 + -0.6666666665 Combine like terms: -2.788866755 + -0.6666666665 = -3.4555334215 x = -3.4555334215 Simplifying x = -3.4555334215Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.1222000885, -3.4555334215}Solution
x = {2.1222000885, -3.4555334215}
| (2x^2)+34x+144=0 | | 4N+13=57 | | 8y-12=30 | | 4x^2+128=0 | | 6.55a+2.2b=1440 | | -3x-6=3x-60 | | (14x)+180=7000 | | (14x)+(142)=7000 | | 3x+16=5(x+4)+2 | | (x+iy)(1-i)+(2x+3iy)(1+i)=7 | | -6=3(3x+1)+9 | | Mm/ow= | | -3x-5=-x-29 | | 7x^2+24x^2=22500 | | (M*n)/(p*q) | | m/7-1=11 | | 0.3+0.7x=5.5 | | SinX/10X | | 5a+5-4a-4-a-1= | | (14x)+(4y)=7000 | | (3x-y)squared+(x-5)squared=0 | | 3(2x-1)-(x+7)=0 | | W^2-40w+36=0 | | 9/7x=-21/4 | | 2a+2b+2c=40 | | f(x)=x^2+10x-98 | | 3(2-7x)=4-(2x+1) | | (x-1)(x+4)(x-7)=0 | | 11/2÷4 | | 1/6•3 | | (y^2-8)(7y^2-7y+7)= | | (t-6)(3t-6)=0 |